DEVELOPMENT OF GOOGLE SITES-BASED TOSAURBA WEBSITE MEDIA IN LEARNING ISLAMIC RELIGIOUS EDUCATION IN ELEMENTARY SCHOOLS - Aeni, Ani Nur; Nurlela, Dian; Sartika, Sartika; br Ginting, Trisni Karo Ulina (Universitas Islam Madura, 2025)
This research aims to develop a website-based digital learning media called Toseurba (Tolerance for Religious Unity), which is designed to increase the insight and understanding of grade IV elementary school students regarding the values of tolerance between religions through the subject of PAI. The research method used is Design and Development (D&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The research subjects consisted of 41 grade IV students at SDN Cimalaka III. Validation of the product was carried out by media experts and subject matter experts through a Likert scale questionnaire, with results showing that the product feasibility level in the category was very high, with an average score of 97.95%. The implementation of the product in the learning process showed a significant increase in students' understanding of tolerance material, where 36 out of 41 students managed to achieve the (KKM) in the post-test evaluation. Additionally, student responses to the Toseurba website have been overwhelmingly positive, with an average percentage of 99.2% stating that the medium is engaging, easy to understand, and enjoyable. The implications of this study show that the integration of digital technology in PAI learning not only increases the effectiveness of material delivery, but also contributes to the formation of students' character, especially in instilling the value of tolerance from an early age. Therefore, the development of similar digital media needs to be considered by educators and policymakers as an innovative strategy in multicultural-based character education in elementary schools.